Identification and diversity of birds in gayo lues district pining forest in leuser ecosystem area - Zurfika Ramayanti; Khairil Khairil; Abdullah Abdullah; Devi Syafrianti; Ismul Huda (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Pining Forest Pining District is one of the Leuser ecosystem areas. High population activities such as illegal logging, forest conversion, and hunting of wild animals, and land clearing by burning forests in the Pining forest area Pining District will impact on bird diversity. Observing data was carried out in August 2019. The purpose of this study was to determine the level of bird diversity in the Pining forest area of Gayo Lues Regency. The method used in this study is the direct observation method combined with line transect. The results of research conducted in the Pining Forest found 30 species of birds consisting of 21 families. Identification of bird spescies found in the Pining Forest of Gayo Lues Regency with the most species of bird families, namely from the families of Estrildidae and Rhipiduridae, each of which were 3 bird species. Bird Diversity in Pining Forest Gayo Lues District in the Leuser Ecosystem is classified as high (Ĥ = 3.0455) in primary forests, while (Ĥ = 2,434) in secondary forest habitat.Keywords: Species Diversity, Birds, Pining Forest. Hutan Pining Kecamatan Pining adalah salah satu kawasan ekosistem Leuser. Tingginya aktivitas penduduk seperti alih fungsi hutan, penebangan liar, dan perburuan satwa liar, dan pembukaan lahan dengan cara membakar hutan di kawasan hutan Pining Kecamatan Pining akan berimbas terhadap keanekaragaman burung. Pengamatan data telah dilaksanakan pada bulan Agustus 2019. Tujuan penelitian ini adalah untuk mengetahui tingkat keanekaragaman burung di kawasan Hutan Pining Kabupaten Gayo Lues. Metode yang di gunakan dalam penelitian ini adalah metode observasi langsung (direct observation) dikombinasikan dengan line transect. Hasil penelitian yang dilakukan di Hutan Pining didapatkan 30 spesies burung yang terdiri dari 21 famili. Identifikasi jenis burung yang ditemukan di Hutan Pining Kabupaten Gayo Lues dengan famili spesies burung terbanyak yaitu dari famili Estrildidae dan Rhipiduridae yang masing-masing sebanyak 3 spesies burung.Keanekaragaman Burung di Hutan Pining Kabupaten Gayo Lues dalam Kawasan Ekosistem Leuser tergolong tinggi (Ĥ= 3.0455) pada hutan primer, sedang (Ĥ= 2,434) pada habitat hutan sekunder.Kata kunci: Keanekaragaman Spesies, Burung, Hutan Pining.